Characterization of the clonal profile of MRSA isolated in neonatal and pediatric intensive care units of a University Hospital - Pereira, Valeria Cataneli [UNESP]; Moraes Riboli, Danilo Flavio [UNESP]; Ribeiro de Souza da Cunha, Maria de Lourdes [UNESP] (Biomed Central Ltd, 2014)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) are important pathogens in neonatal and pediatric intensive care units, which can cause severe infections in hospitalized children. Detection of the mecA gene and classification of the staphylococcal cassette chromosome mec (SCCmec) permit the characterization of MRSA strains isolated from infections caused by these microorganisms. In contrast, pulsed-field gel electrophoresis (PFGE) is used to type MRSA clones. This method is commonly used to analyze the epidemiology of bacteria causing nosocomial infections. The objective of this study was to detect and characterize MRSA isolated from clinical specimens of children hospitalized in the neonatal and pediatric intensive care units of the University Hospital of the Botucatu Medical School.Methods: A total of 119 S. aureus strains were isolated from clinical specimens and the mecA gene was detected by PCR. SCCmec was detected by multiplex PCR and the clonal profile was analyzed by PFGE.Results: The mecA gene was detected in 17.6% (21/119) of the isolates; 42.9% (9/21) of MRSA were characterized as SCCmec type III and 57.1% (12/21) as type IV. Analysis of the clonal profile of these strains revealed three distinct clones, with SCCmec type III being related to the Brazilian endemic clone and type IV to clones JCSC4469 and USA800.Conclusions: Replacement of clonal groups occurred in the neonatal and pediatric units over the period studied, a fact highlighting the importance of improving hygiene practices and control measures of nosocomial infections in these units.
Keywords: Nosocomial infections; NICU; PICU; MRSA